PENERAPAN ISLAM MULTIKULTURAL DI SEKOLAH ISLAM TERPADU NURUL WAHDAH - Shah Khumainy; Ubabuddin Ubabuddin (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study explores the application of multicultural Islamic education within the context of SMP Islam Terpadu Nurul Wahdah. In an increasingly diverse and interconnected world, fostering tolerance and mutual respect among students of various cultural and religious backgrounds is crucial. This research examines the strategies employed by the school to integrate multiculturalism into its curriculum, including classroom activities, extracurricular programs, and community engagement initiatives. Utilizing a qualitative approach, data were gathered through interviews, observations, and document analysis. The findings indicate that SMP Islam Terpadu Nurul Wahdah successfully incorporates Islamic values of tolerance, justice, and respect in its educational framework, promoting an inclusive environment that encourages dialogue among students from diverse backgrounds. Furthermore, the implementation of multicultural principles has significantly enhanced students’ social skills, empathy, and awareness of social issues. Despite the positive outcomes, the study identifies several challenges in the effective implementation of multicultural education, including resistance to change and limited resources. Nevertheless, the research concludes that the integration of multicultural Islamic education is essential in preparing students to navigate and contribute positively to a pluralistic society. This study serves as a reference for other educational institutions seeking to foster multicultural understanding and harmony in their pedagogical practices.